Self and Cultural Translation: A Study of Islamic Feminism in Leila Aboulela’s the Translator - Javeed, J. Sumaiya; Rathna, P. (International Journal of Psychosocial Rehabilitation, 2020)
Migration of women has always been an important component of international migration. Women often migrate officially as dependent family members of other migrants or to marry someone in another country. By means of translation, immigrant women define and re-mould their identities and challenge the notion of place and translation itself. Leila Aboulela is an Egyptian born Sudanese and British educated writer. The Translator is her first novel, published in 1999. It is a story about a young Sudanese widow Sammar living in Scotland and her sprouting relationship with Islamic scholar Rae. The novel The Translator is the clear evidence of the personal difficulties encountered by Immigrant Muslims in particular Muslim women, in the practice of their religion in non-Muslim societies and the ways that religious faith, gender and class are translated among different cultures. It also addresses Aboulela’s obstinate stance against the boundaries of gender, culture, faith and religion. This paper aims to explore the representation of a Muslim woman character by a Muslim woman writer and the role of cultural transgression, religious and migrant identity with reference to Aboulela’s The Translator through the lens of Islamic feminism.